2019
DOI: 10.5765/jkacap.180027
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Depression and School Life on the Quality of Life of Korean Child and Adolescent Patients with Attention-Deficit/Hyperactivity Disorder: A Comparison of the Perspectives of the Patients and Their Caregivers

Abstract: This study aimed to compare the quality of life reported by patients with attention-deficit/hyperactivity disorder (ADHD) to the patients' quality of life as reported by their caregivers. In addition, it aimed to examine how emotional problems, including depression and anxiety, and the severity of the symptoms affect the quality of life reported by the patients and their caregivers. Methods: The patients' quality of life and their degree of depression and anxiety were measured using the Pediatric Quality of Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…The correlation between quality of life in the subjects with ADHD, analyzed using the PedsQL, and the subscales of the K-YSR showed that the externalization and internalization scale, depression/anxiety scale, inferiority scale, social immaturity scale, thought problems scale, and the aggression scale, as well as the DSM-oriented emotion, anxiety, hostile rebellion, and behavioral disturbance scales correlated with all four subitems and total scores of the PedsQL. This association with emotional factors is consistent with previous research [16]. In addition, the results of this study showed that aggressive behavior (among the syndrome scales), externalization (among the broad band scales), and conduct problems (among the DSM-oriented scales) were significantly associated with quality of life in subjects with ADHD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlation between quality of life in the subjects with ADHD, analyzed using the PedsQL, and the subscales of the K-YSR showed that the externalization and internalization scale, depression/anxiety scale, inferiority scale, social immaturity scale, thought problems scale, and the aggression scale, as well as the DSM-oriented emotion, anxiety, hostile rebellion, and behavioral disturbance scales correlated with all four subitems and total scores of the PedsQL. This association with emotional factors is consistent with previous research [16]. In addition, the results of this study showed that aggressive behavior (among the syndrome scales), externalization (among the broad band scales), and conduct problems (among the DSM-oriented scales) were significantly associated with quality of life in subjects with ADHD.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the severity of symptoms in ADHD patients may also affect their quality of life by impacting their daily functions and their interactions and relationships with family members [15]. Although there have been many studies on the effects of emotional states on the quality of life of adolescents with ADHD in Korea [16], few studies have studied juvenile inmates with ADHD, especially with a focus on their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of good correlation between child self-reporting and parent proxy-reporting in the current study was also documented in earlier studies [7,26,27]. This finding is not consistent with results of other studies [28,29]. This may be due to the parents' higher degree of concern, frustration, and more guarded view of their child's well-being and their tendency to be overprotective of their chronically ill child [25].…”
Section: Discussioncontrasting
confidence: 77%
“…Self-report questionnaires are easy to administer and frequently used to assess metacognitive ability; however, these self-reports present several limitations, for example, it is difficult to evaluate for people with difficulties in self reference (e.g., autism spectrum disorders) and who are still developing (e.g., adolescence) ( Sebastian et al, 2008 ). In psychology, parental reports are commonly used to assess temperament ( De Los Reyes and Kazdin, 2005 ; Fox et al, 2005 ; Durbin et al, 2007 ; Hash et al, 2019 ), emotional difficulties ( Theunissen et al, 2019 ), behavioral problems ( Fujikawa et al, 2016 , 2018 ), and depression ( Park et al, 2019 ) in children, as they are often incapable of accurately reporting how they feel. Yet, important questions remain concerning whether the constructs assessed by the parental reports can be used to verify metacognitive ability in children.…”
Section: Introductionmentioning
confidence: 99%